ANALISIS TERJADINYA SLIP PADA KOPLING DI UNIT SCANIA P 124 CB 8x4 NZ 420 - Rasma Rasma; Hendro Purwono; Riki Effendi (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2019)
In the operation of the unit whose successor does not use a hydraulic system, the role of the clutch is very important in transmitting power from the engine to the transmission. However, the clutch can only slip so that it can no longer function to forward power from the engine to the transmission. This can be caused by several things, including: wear on the clutch material, the presence of oil in the field of clutch surface, and spring damage to the clutch. On Scania P 124 CB 8x4 NZ 420 units this slip on clutch problem also occurs so research needs to be done to find the main cause. The method used in this study is to carry out checks and measurements and then the results are compared with the standard values that have been determined. The result shows that the cause of the slip on the clutch on the Scania P 124 CB 8x4 NZ 420 unit is 1) the presence of oil that wet the coupling surface is caused by a damaged seal shaft; 2) wear on clutch components namely clutch disc and pressure plate. To keep the seal shaft in good condition, regular and regular oil changes must be made and when the replacement of the seal shaft must be in accordance with the part number so that the possibility of the same problem can be reduced.